Patent output and patent transfer network in China universities: Moderating roles of absorptive capacity and desorptive capacity - Jia, Hongjun; Zhou, Jing (Heliyon, 2024)
Although absorptive capacity and desorptive capacity has been widely present in university-industry relationships, there has been no research on their potential impact on the relationship between university patent output and university patent transfer network. We constructed datasets of patent applications and patent transfers to firms from 383 universities between 2002 and 2021 in China, and empirically demonstrated the effect of the patent output on university patent transfer network using negative binomial regression models. We also examined the moderating effects of absorptive capacity and desorptive capacity. The results reveal that university patent output positively affects the size and the connection strength of the university patent transfer network. Technology transfer offices and satellite institutions, for desorptive capacity in universities, negatively moderate the relationship between the university patent output and the university patent transfer network, respectively. For absorptive capacity in firms, research and development intensity of new products and the level of research and development personnel input, respectively, have a positively moderate effect on the relationship between the university patent output and the university patent transfer network. Our research provides insights into the dynamics of the university patent transfer network; especially against the backdrop of a sharp increase in university patent output and insufficient development of the university patent transfer network, this study provides evidence to the substitution effect of desorptive capacity in universities and the bidirectional effect of absorptive capacity in firms. •The rapid growth of UPO not only consumes a significant amount of financial resources but also presents a serious challenge to how universities develop dynamic capabilities. Promoting patent transfer through AC and DC is key to driving the high-quality development of universities.•Our study is based on datasets of patent applications and patent transfers from 383 Chinese universities between 2002 and 2021. We employed a negative binomial regression model to analyze the impact of UPO on UPTN and examined the moderating effects of AC and DC.•The results demonstrate that UPO has a positive impact on the scale and connection strength of UPTN. UTTO and USI have a negative moderating effect on the relationship between patent output and the patent transfer network. R&D intensity of new products and the level of R&D personnel input, respectively, have a positive moderate effect on the relationship between patent output and the patent transfer network.